2020
DOI: 10.1055/s-0040-1710522
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Neonatal Respiratory Care: Current Evidence and Practical Approach

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic has urged the development and implementation of guidelines and protocols on diagnosis, management, infection control strategies, and discharge planning. However, very little is currently known about neonatal COVID-19 and severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infections. Thus, many questions arise with regard to respiratory care after birth, necessary protection to health care workers (HCW) in the delivery room and neonatal intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
62
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 59 publications
4
62
0
16
Order By: Relevance
“…Like in other age groups, major transmission routes in neonates are respiratory droplets, contact transmission and aerosol transmission (20). Data in this population are scarce, from small series included in larger studies on pediatric cases, in which, unlike adults, clinical manifestations have been reported to be mild (21). Interestingly, the proportion of severe and critical cases reported in children is inversely correlated with their age, and infections in infants <1 year old have been more severe (22).…”
Section: Introductionmentioning
confidence: 95%
“…Like in other age groups, major transmission routes in neonates are respiratory droplets, contact transmission and aerosol transmission (20). Data in this population are scarce, from small series included in larger studies on pediatric cases, in which, unlike adults, clinical manifestations have been reported to be mild (21). Interestingly, the proportion of severe and critical cases reported in children is inversely correlated with their age, and infections in infants <1 year old have been more severe (22).…”
Section: Introductionmentioning
confidence: 95%
“…A recent (as we write this commentary) review identified 27 publications describing 217 newborns born to mothers with COVID-19, of which 21 publications describing 187 newborns were from China. 3 Of the 217 newborns, 7 (3%) had evidence of SARS-CoV-2 infection: 3 had positive serum levels of immunoglobulin G and immunoglobulin M antibodies with negative polymerase chain reaction (PCR) test results, and 4 had positive PCR test results. Beyond the immediate postnatal period, in several case studies, authors report positive SARS-CoV-2 test results in symptomatic newborns in the first month of life, and new reports are published frequently.…”
mentioning
confidence: 99%
“…Beyond the immediate postnatal period, in several case studies, authors report positive SARS-CoV-2 test results in symptomatic newborns in the first month of life, and new reports are published frequently. [3][4][5][6][7] The mechanism of neonatal infection is unclear. Vertical transmission during pregnancy is not thought to be likely; SARS-CoV-2 test results on placenta, umbilical cord, amniotic fluid, vaginal secretions, and breast milk samples have uniformly been negative.…”
mentioning
confidence: 99%
“…Hopefully, several extreme measures will not be needed, especially if very rapid and reliable tests become available. For the time being, it seems reasonable to use the available published COVID-19 NICU protocols [13][14][15], and increase surveillance when case-rates rise locally; unfortunately probably a necessary condition we will continue to face for some time.…”
mentioning
confidence: 99%